1995
DOI: 10.1515/jpem.1995.8.1.67
|View full text |Cite
|
Sign up to set email alerts
|

Male Pseudohermaphroditism with 5-α-Reductase Deficiency: Report of Two New Familial Cases. The Importance of Early Diagnosis

Abstract: We report two new familial cases of male pseudohermaphroditism due to 5-alpha-reductase deficiency, from the south of Spain. They were born with ambiguous genitalia and were reared as females. At the time of puberty, both brothers virilized partially and underwent a change of gender role from female to male with a stormy psychic readjustment period. We stress the value of the prolonged chorionic gonadotropin test for an early diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 11 publications
(1 reference statement)
0
2
0
Order By: Relevance
“…Not surprisingly, coping with these rare conditions, especially with the unexpected pubertal changes, was highly unsettling and caused psychological problems in all participants. These findings illustrate that “psychic disturbances” occur not only in persons transitioning but also in individuals remaining in the assigned gender (Aguilar-Diosdado et al, 1995). All had noted a sense of difference from other women or men when growing up.…”
Section: Methodsmentioning
confidence: 75%
See 1 more Smart Citation
“…Not surprisingly, coping with these rare conditions, especially with the unexpected pubertal changes, was highly unsettling and caused psychological problems in all participants. These findings illustrate that “psychic disturbances” occur not only in persons transitioning but also in individuals remaining in the assigned gender (Aguilar-Diosdado et al, 1995). All had noted a sense of difference from other women or men when growing up.…”
Section: Methodsmentioning
confidence: 75%
“…For 17β-HSD-3 deficiency, these studies were conducted in Israel ( n = 15; Rosler, Silverstein, &Abeliovich, 1996) and Brazil ( n = 10; Mendonca et al, 2000). Studies on both conditions from European countries showed sample sizes ranging from one to four (e.g., Aguilar-Diosdado, Gavilán-Villarejo, Escobar-Jiménez, Beltrán, &Grión, 1995; Boudon et al, 1995; Leinonen, Dunkel, Perheentupa, &Vihko, 1983; Wieacker &Von Mühlendahl, 1996). Knowledge about the genetic basis is continuously growing.…”
Section: Androgen Biosynthesis Deficienciesmentioning
confidence: 99%